2021
DOI: 10.4085/1062-6050-126.20
|View full text |Cite
|
Sign up to set email alerts
|

Performance After Concussion in National Hockey League Players

Abstract: Context Concussions in ice hockey players are an interesting area of study due to the fast-paced and high-impact nature of the sport. Recently, researchers have focused on player performance after return from concussion to evaluate subclinical deficits that were previously missed. Objective To examine National Hockey League (NHL) player performance from 2013 to 2019 and compare performance before a concussion with performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Excellent short-term recovery from concussion in NHL players is reflected in other reports on NHL performance. Neustadtl et al 20 assessed NHL player performance during the 5 games before and the 5 games after a concussion injury and found no significant change in performance measures. Similarly, Kuhn et al 12 assessed NHL player performance at 5 games before and after concussion and found no significant differences in standard performance metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent short-term recovery from concussion in NHL players is reflected in other reports on NHL performance. Neustadtl et al 20 assessed NHL player performance during the 5 games before and the 5 games after a concussion injury and found no significant change in performance measures. Similarly, Kuhn et al 12 assessed NHL player performance at 5 games before and after concussion and found no significant differences in standard performance metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Our RTP rate is similar to that reported in NFL and National Hockey League. 13 , 23 , 28 NBA players returned, on average, 37.3 days after injury, but this varied widely (range, 2-291 days), probably skewed by those with season-ending injuries. The median days before RTP was 7 with an IQR of 16.…”
Section: Discussionmentioning
confidence: 99%